GRAMMATICAL COHESION OF PERSONAL PRONOUNS IN CHILDREN’S STORIES, ADOLESCENT STORIES, AND ADULT STORIES OF KOMPAS - Siti Sukriyah; Sumarlam Sumarlam; Djatmika Djatmika (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This  study  aimed  to  describe  the  discourse  coherence  supported by aspects of gramatical cohesion is limited to the use of personal pronouns in the  rubric of cernak, roman, and cerpen in Kompas Newspaper. this research belongs to descriptive  qualitative. The data are obtained by review method with note technique as further technique. The data of this research are linguistic data taken from cernak, roman, and cerpen rubric of Kompas newspaper. The object of this research is personal pronouns grammatical cohesions in cernak, roman, and cerpen rubric of Kompas newspaper. Data analysis is done by identifying of the grammatical cohesion type of personal pronouns, then classify and describe the aspects of that grammatical cohesion. And then, the data is interpreted to get the conclusions. The results of this research that grammatical cohesion aspects of the personal pronouns in every rubric. the first, second, and third personal pronouns is found in every rubric. In the cernak is more likely has the form of the free third person as well as roman. Meanwhile, for the short story of adult has the plural third person because the plot of the short story of adult is more complex and have more figures than cernak or roman. The results of the data analysis showed that cernak, roman, and cerpen rubric of Kompas newspaper is a discourse coherent because it is supported by a slick lexical cohesion markers. Keywords: grammatical cohesion, Kompas, personal pronouns, rubric